Measurement of σ(pp̄→Z)·Br(Z→ττ) at √s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
We present a measurement of the cross section for Z production times the branching fraction to τ leptons, σ·Br(Z → τ+τ-), in pp̄ collisions at √s = 1.96 TeV in the channel in which one τ decays into μνμν τ, and the other into hadrons + ντ or eνeντ. The data sample corresponds to an integrated luminosity of 226 pb-1 collected with the D0 detector at the Fermilab Tevatron collider. The final sample contains 2008 candidate events with an estimated background of 55%. From this we obtain σ·Br(Z → τ+τ-) = 237 ± 15(stat) ± 18(sys) ± 15(lum)pb, in agreement with the standard model prediction. © 2005 The American Physical Society.